A possible additional body in eclipsing binary system HS 2231+2441 - A. P. Vidmachenko; Ya. O. Shlakhetska; Ya. O. Romanyuk (Вісник Астрономічної школи, 2016)
Analysis of the light curves of eclipsing binary systems HS 2231+2441, obtained with the 36-cm telescope, is made. In processing the photometric data on eclipses by method of timing, obtained evidence for the existence of a third body in the system.